Potential Antitumour Activity of Gmelina asiatica Aerial Parts Against Dalton Ascites Lymphoma in Mice - Merlin, N.J.; Parthasarathy, V. (Asian Journal of Chemistry, 2010)
The aim of the present study is to evaluate the effect of chloroform extract of aerial parts of Gmelina asiatica (CGA) against Dalton's Ascitic Lymphoma (DAL) in Swiss Albino mice. Dalton's Ascitic Lymphoma cells were injected intraperitoneally (106 cells) to the mice. Two days after cells injection the animals were treated with 200 and 400 mg/kg of CGA for 14 days. Five-fluorouracil (20 mg/kg) was used as reference drug. On day 15, cancer cell number, packed cell volume, decrease in tumour weight of the mice, increase in life span and hematological para-meters were evaluated and compared with the same parameters in control. A significant increase in the life span and a decrease in the cancer cell number and tumour weight were noted in the tumour-induced mice after treatment with chloroform extract of Gmelina asiatica. The hematological parameters were also normalized by chloroform extract of Gmelina asiatica in tumour-induced mice. These observations are sugges-tive of the protective effect of chloroform extract of Gmelina asiatica against Dalton's Ascitic Lymphoma.